Physicochemical Studies of Bore Wells Water of Different Places in Chennai, India - Dayalan, A.; Karthik, A.; Benin Raj, T.; Prabhu, S.; Jagan, K. (Asian Journal of Chemistry, 2016)
Physicochemical studies such as pH, chemical oxygen demand, total and permanent hardnesses and hardness due to magnesium, chloride, sulphate, phosphate and nitrate contents, total dissolved solids and conductivity of various bore well waters were carried out for thirty samples collected at different parts of Chennai especially in the central region during April 2004 and their water qualities were assessed.